Processes of community change and social action - Claremont Symposium on Applied Social Psychology (2005); Omoto, Allen Martin (Mahwah, N.J. : Lawrence Erlbaum Associates, 2005)
This volume--an outgrowth of the annual meeting of the Claremont Symposium on Applied Social Psychology--focuses on examples of social change and community action, and the processes at work in creating change. The presenters engaged each other and the audience in thinking about how best to create and sustain social change. This volume represents a product of their cumulative insight, research results, and perspectives, including chapters from each of the symposium presenters, as well as a few selected chapters from other noted scholars. Taken as a whole, the volume is highly accessible and pre.
6 A Benefit-and-Cost Approach to Understanding Social Participation and Volunteerism in Multilevel Organizations7 Social Capital in Democratic Transition: Civil Society in South Africa; 8 Social Participation and Social Trust in Adolescence: The Importance of Heterogeneous Encounters; 9 Designing Interventions to Promote Civic Engagement; About the Contributors; Name Index; Subject Index
"Claremont Symposium on Applied Social Psychology."
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Voluntarism -- Congresses; Social action -- Congresses; Political socialization -- Congresses; Civil society -- Congresses; Action sociale -- Congrès.; Socialisation politique -- Congrès.; Société civile -- Congrès.; Bénévolat -- Congrès.; SELF-HELP -- Personal Growth -- Success; Civil society; Political socialization; Social action; Voluntarism; Conference papers and proceedings